PENEMUAN MAKNA HIDUP MELALUI TAZKIYÂT AL-NAFS; SEBUAH AKTUALISASI NILAI-NILAI SUFISTIK DALAM KEHIDUPAN - Komarudin Komarudin (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2011)
The limitation of human ability to make ethical assessments against each other only a behavioral manifestation of outer (not inner), while that could see farther, with a very high accuracy, the behavior of trajectories and the inner self is only Allah. Likewise, none able to ensure his good deeds are accepted by God, but that is just a hope. Therefore, it should be done every human being is always to implement muhasabah al-nafs, the introspection of himself every time. This paper tried to discuss efforts to the discovery of meaning in life through the process tazkiyat al-nafs, the inner actualization muhasabah against human behavior. In Sufi spiritual existence, which is often referred to as al-qalb, is a key determinant of good and bad behavior of human outer side. Therefore, the maintenance of probity and conduct careful management the key to success in living life the human world and the hereafter, to the pleasure of Allah swt. Nafs tazkiyatun process will produce really nice of the life achievements of happiness in this world and the happiness and salvation in the hereafter. This is not another ideals of every Muslim, who always want a happy life in the world and the hereafter, and survived the fire of hell, as prayer is often offered,